Prices of Biofuels and Related Commodities: An Example of Combined Economics and Graph Theory Approach - Ondrej Filip; Karel Janda; Ladislav Kristoufek (Charles University in Prague, Institute of Economic Studies (IES), 2017)
The article investigates the connections between the prices of biofuels and many traded commodities and other relevant assets in Europe, USA and Brazil. The analysis uses a comprehensive dataset covering price data for 32 relevant traded titles over the period 2003-2015. Main contribution of this article is a combination of minimum spanning tree and hierarchical tree approaches with expert economic understanding of biofuels market leading to identification of price connections in a complex trading system. Our analysis of mutual price connections discovers the major defining features of world leading biofuels markest over the last decade. We provide characteristics of main bioethanol and biodiesel markets with respect to technical and local features of the production and consumption of particular biofuels.
Keywords: C38; Q16; Q42; 330; biofuels; networks; minimal spanning tree; hierarchical tree